Pengaruh Strategi Branding Lembaga Pendidikan Islam terhadap Loyalitas Peserta Didik Madrasah Aliyah Negeri - Devi Fatwanti; Iwan Irwandi; Moch Faisal; Ilzamudin; Ahmad Qurtubi; Agus Gunawan (Irfani, 2026)
This study analyzes the influence of the branding strategy of Islamic educational institutions on loyalty in students of Madrasah Aliyah Negeri. Using a quantitative approach with a simple linear regression design, this study involved 88 students of Madrasah Aliyah Negeri who were selected through total purposive sampling. Data was collected using branding strategies and loyalty scales) that have been tested for validity and reliability. The hypothesis that the branding strategy has a positive effect on student loyalty is evidenced by the determination coefficient R² = 0.473, the F-value = 66.691 (Sig. = 0.000), and t = 8.166 (p < 0.001). Branding strategies have been proven to have a positive and significant effect on the loyalty of Madrasah Aliyah Negeri students. This research was compiled by synthesizing the concept of Educational Services Marketing (such as marketing and branding mix strategies) with the dimension of Consumer Psychology which is focused on student perception and loyalty. This is done to understand the decision-making mechanism and the emotional attachment of students to the institution. This research makes a theoretical contribution in enriching the treasures of Islamic Education Management, especially through the integration of service marketing concepts with educational consumer behavior.